LEXICOLOGY AND ITS PRIMARY ROLES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes in detail the main tasks of lexicology, the general problems of lexicology in terms of the vocabulary of all languages, the collection and systematization of terms used in the language. Uzbek language, the main problems of lexicology, the rules of practical use and the development of lexicon.